Emphasis on Systemic Therapy in Women With Pelvic Bone Metastasis at Time of Diagnosis of Cervical Cancer. (November 2018) - Manders, Dustin B.; Sims, Travis T.; Albuquerque, Kevin V.; Carlson, Matthew J.; Richardson, Debra L.; Kehoe, Siobhan M.; Miller, David S.; Lea, Jayanthi S.
Abstract : Objective: Cervical cancer presenting with metastases to the bony pelvis is rare. No available literature addresses the treatment and prognosis of these patients. Our objective was to review our experience treating women with this rare presentation. Methods: We performed a review of all patients treated for cervical cancer at a single institution between January 1, 2007 and November 30, 2014. All patients had pretreatment imaging with computed tomography or positron emission tomography/computed tomography. Included patients had evidence of pelvic bone metastases by imaging before initiation of treatment. Results: A total of 349 women were treated for cervical cancer during the study interval. Of these, 13 (3.7%) were identified as having pelvic bone metastases at initial presentation. Four of 13 patients had pelvic-confined disease and were treated with curative-intent radiation. The remainder had disseminated disease and were treated with palliative radiation. Only one complete response was seen. Seven patients received salvage chemotherapy. The median overall survival was 8.5 months. Survival was statistically similar in those who received palliative rather than curative radiotherapy (8.7 vs. 8.1 mo, P =0.76) and in those who received any postradiation chemotherapy (8.9 vs. 6.1 mo, P =0.066). Chemotherapy with bevacizumab resulted in the only 2 long-term survivors (both alive at 32.4 and 37.5 mo). All others have died of disease. Conclusions: Cervical cancer metastatic to the bony pelvis at initial presentation portends a dismal prognosis. Patients should be informed about this poor prognosis, and allowed to make an informed decision when considering curative-intent versus palliative treatment. Incorporation of bevacizumab appears to improve survival.